The - Cholle, Francis P.
A dynamic new way to understand intuition, already implemented around the world at top companies and business schools Neuroscience shows that instinct has a leading role in complex decision-making, yet imaginative play is the most direct means of activating our creativity and problem-solving abilities. Based on over 20 years of Cholle's wide-ranging professional experience and insights, The Intuitive Compass offers a fascinating new approach to innovative problem-solving, decision-making, and sustainable value creation. Through a concept known as Intuitive Intelligence, Cholle shows how anyone can improve creative brainpower by harnessing the balance between reason and instinct